PENGARUH RASIO LIKUIDITAS, RASIO LEVERAGE DAN RASIO AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Parhusip, Poltak Theodorus; Sitanggang, Abdonsius; Purba, Antonius M.; Lumban Gaol, Romasi (Jurnal Riset Akuntansi & Keuangan, 2024)
This research aims to empirically determine the impact of liquidity ratio, leverage ratio, and activity ratio on profit growth in pharmaceutical companies listed on the Indonesia Stock Exchange. The study involves ten pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2019-2021 as the sample. Secondary data using documentation techniques were employed for the study, and the data analysis utilized multiple linear regression.. The research results revealed a multiple linear regression equation: Y = -93.825 + .217X1 – 0.703X2 + 0.606X3. According to the t-test, each ratio individually has a significant influence on profit growth. In other words, these three ratios collectively contribute significantly to understanding the factors influencing profit growth in pharmaceutical companies on the Indonesia Stock Exchange. The F-test indicates that simultaneously, liquidity ratio, leverage ratio, and activity ratio have a significant impact on profit growth in pharmaceutical companies. This suggests that liquidity ratio, leverage ratio, and activity ratio collectively influence profit growth in pharmaceutical companies listed on the Indonesia Stock Exchange. The coefficient of determination, with a value of 0.655, implies that 65.5% of the variance in profit growth can be explained by these three ratios, while the remaining 34.5% is attributed to other factors. For future research, it is recommended that researchers increase the sample size and incorporate additional variables to obtain a more comprehensive and accurate analysis.